2016
DOI: 10.12741/ebrasilis.v9i2.586
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos de Nidificação de Polistes canadensis (Linnaeus) (Hymenoptera: Vespidae) em Área Urbana

Abstract: Resumo. Visando compreender a ecologia de nidificação de Polistes canadensis (Linnaeus) em áreas urbanas, foram realizadas buscas ativas por colônias no Campus da Universidade Federal do Rio Grande do Norte. Foram encontradas 442 colônias em sete materiais como substrato para nidificação, sendo 98% em edificações humanas. Concreto e metal foram os substratos mais utilizados para nidificação das vespas, podendo ser justificado pela maior presença desses materiais no ambiente e ainda, pela retenção de calor que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…For instance, M. cerberus, Mischocyttarus metathoracicus and Polybia occidentalis were registered in almost all types of nesting substrate, but Mischocyttarus montei showed less plasticity in relation to the substrate chosen, being registered only in metal substrates. The apparent preference of the wasp for nesting in masonry might be related to the greater offer of this substrate in comparison to the others, and this fact reinforces the idea of a good adaptation of this species in urban environments (Virgínio et al, 2016).…”
Section: Speciessupporting
confidence: 64%
See 1 more Smart Citation
“…For instance, M. cerberus, Mischocyttarus metathoracicus and Polybia occidentalis were registered in almost all types of nesting substrate, but Mischocyttarus montei showed less plasticity in relation to the substrate chosen, being registered only in metal substrates. The apparent preference of the wasp for nesting in masonry might be related to the greater offer of this substrate in comparison to the others, and this fact reinforces the idea of a good adaptation of this species in urban environments (Virgínio et al, 2016).…”
Section: Speciessupporting
confidence: 64%
“…In sequence, the second category most used by wasps was metal, this preference was probably related with a phenomenon known as "heat islands" (Lola et al, 2013), the accumulated heat over the metallic superficies provides suitable conditions for the colonies to develop, it was previously shown in studies with social insects (Virgínio et al, 2016).…”
Section: Speciesmentioning
confidence: 90%
“…The second category most used by wasps was metal tubes. Some authors (Lola et al, 2013;Virgínio et al, 2016) have suggested that this preference was probably related with a phenomenon known as "heat islands"; the accumulated heat over the metallic superficies provides suitable conditions for the colonies to develop. We cannot rule out this fact, but in the south of the Iberian Peninsula very high temperatures are recorded in July and August, which can cause the death of the colony.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, social wasps may act as pollinators when visiting flowers (Clemente et al, 2012), detritivores when foraging on decaying fruits and animal carcasses (Moretti et al, 2011), and predators when foraging on agricultural pests (e.g., caterpillars) (Elisei et al, 2010). As a result, social wasps are part of a complex intra and interspecific ecological web that is yet to be fully comprehended (Menezes et al, 2014;Virgínio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Alvarenga et al, 2010;Jacques et al, 2012;Naldoski, 2013;Torres et al, 2014;see Barbosa et al, 2016). They show the relation between many species of social wasps and their environments, such as how some species found in urban areas depend exclusively on natural vegetation, whereas other prefer artificial substrates (Alvarenga et al, 2010;Sinzato et al, 2011;Castro et al, 2014;Virgínio et al, 2016). Moreover, as humans continue to change their RESEARCH ARTICLE -WASPS environment, some species seem to change their nesting preferences as well (Torres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%